Revitalisasi Peran Guru sebagai Pembina Akhlak melalui Pendekatan SQ dan EQ dalam Islam - Muthmainnah Choliq; Cindy Auliaa Hasanah; Ariz Rahmi Rabbani; Aufa Rofiqi; Sofiyana Habibah (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
This study discusses the importance of revitalizing the teacher’s role as a moral guide through the integration of emotional intelligence (EQ) and spiritual intelligence (SQ) in Islamic education. The background of this study stems from the phenomenon of the declining character of students in the midst of rapid technological advancement and unrestricted information flow. This research uses a library research method using a qualitative approach on literature review by analyzing relevant sources. The results show that teachers hold a central role in shaping the character and personality of students—not only as instructors but also as role models. By integrating EQ values such as empathy, patience, and effective communication, along with SQ values such as sincerity, gratitude, and closeness to God, teachers can create a learning environment that touches students’ emotional and spiritual dimensions. This strategy strengthens the teacher’s example in building students’ morals and addresses the challenges of character education in the modern era. Moreover, the involvement of parents and communities is crucial in creating a supportive educational ecosystem. This research recommends enhancing teacher training in EQ and SQ as a strategic effort to develop students who are not only intellectually intelligent but also morally excellent and spiritually grounded according to Islamic values.